Platinum‐based regimens versus cetuximab in definitive chemoradiation for human papillomavirus‐unrelated head and neck cancer. Issue 1 (11th November 2019) - Beckham, Thomas H.; Barney, Christian; Healy, Erin; Wolfe, Adam R.; Branstetter, Andrew; Yaney, Alexander; Riaz, Nadeem; McBride, Sean M.; Tsai, C. Jillian; Kang, Julie; Yu, Yao; Chen, Linda; et al.
Abstract : For patients ineligible for cisplatin with definitive radiotherapy (CP‐CRT) for locally advanced head and neck squamous cell carcinoma (LA‐HNSCC), concurrent cetuximab (C225‐RT) is a popular substitute. Carboplatin‐based chemoradiation (CB‐CRT) is another option; however, relative efficacies of CP‐CRT, CB‐CRT and C225‐RT are unclear, particularly in the human papillomavirus (HPV)‐unrelated population. We identified 316 patients with stage III‐IVB cancers of the oropharynx (24.7%), larynx (58.2%) and hypopharynx (17.1%) undergoing definitive C225‐RT ( N = 61), CB‐CRT ( N = 74) or CP‐CRT ( N = 181). Kaplan‐Meier and cumulative incidence functions were generated to estimate overall survival (OS), locoregional failure (LRF) and distant metastasis (DM). Cox proportional hazards were used to determine the association of survival endpoints with clinical characteristics. Respectively, 3‐year cumulative incidences for CP‐CRT, CB‐CRT and C225‐RT were: LRF (0.19, 0.18 and 0.48, p  ≤ 0.001), DM (0.17, 0.12 and 0.25, p = 0.32). Kaplan‐Meier estimates for 3 year OS were: CP‐CRT: 71%; CB‐CRT: 59% and C225‐RT: 54%; p = 0.0094. CP‐CRT (hazard ratio [HR] 0.336; 95% confidence interval [CI] 0.203–0.557, p  < 0.01) and CB‐CRT (HR 0.279; 95% CI 0.141–0.551, p  < 0.01) were associated with reduced hazard for LRF on multivariable analysis. CP‐CRT (HR 0.548; 95% CI 0.355–0.845, p  < 0.01) and CB‐CRT (HR 0.549; 95% CI 0.334–0.904, p = 0.02) were associated with a reduced hazard for death on multivariable analysis. Propensity matching confirmed reduced hazards with a combined CP/CB‐CRT group compared to C225‐RT for LRF: HR 0.384 ( p = 0.018) and OS: HR 0.557 ( p = 0.045) and CB‐CRT group compared to C225‐RT for LRF: HR 0.427 ( p = 0.023). In conclusion, CB‐CRT is an effective alternative to CP‐CRT in HPV‐unrelated LA‐HNSCC with superior locoregional control and OS compared to C225‐RT. Abstract : What's new? While head and neck squamous cell carcinoma that are caused by human papillomavirus can be treated relatively well, virus‐negative tumors have a poor prognosis. In this large multi‐institutional study, the authors found that cisplatin‐ and carboplatin‐based regimens—in concurrent chemoradiotherapy—were superior to antibody‐based therapies, with carboplatin‐based regimens representing a more tolerable alternative for patients with virus‐negative tumors.